TANGGUNG JAWAB ATAS KETERLAMBATAN, KERUSAKAN ATAU KEHILANGAN PENGIRIMAN BARANG DI PT. PANDU LOGISTICS - Tira Hana Kristina, Fitika Andraini (Jurnal Ilmiah Dinamika Hukum, 2019)
Freight of goods and passengers in Indonesia With the availability of goods and transportation needed by transportation, there are many entrepreneurs or transportation service companies in the three transportation routes. PT. Pandu Logistik is a company engaged in the transportation of goods which is a legal entity in the Commercial Postal Service as stipulated in article 18 paragraph (1) of Law Number 38 of 2009 concerning Postal. During the process of shipping goods sometimes it does not need to be done with problems, for example regarding expenditures, both originating from nature, human actions or from the nature of the goods themselves. In answering this law, the approach method is carried out using the sociological juridical method with descriptive analytical specifications and the analysis is done qualitatively. The results of this study indicate that the standard agreement in the transportation agreement determined by the carrier according to the position of the parties is not balanced and there is no freedom of transfer to determine the contents of the agreement. Factors that cause ownership change, damage or loss of goods in PT. Pandu Logistics is 2 factors, the first factor which is a factor of PT. Pandu Logistik itself and the second is external factors such as circumstances and accidents that cannot be done in the transportation of goods. The responsibility of PT. Pandu Logistics Semarang for lost or damaged goods that is by way of compensation of 10 times the shipping fee or a maximum of Rp. 1,000,000 (one million rupiah), except if PT. Pandu Logistik Semarang can prove right and wrong that PT. Pandu Logistik Semarang, apart from the negligence and mistakes of the sender of the goods or because there is something about the cargo that does not reach the recipient of the goods, this is what frees PT. Pandu Logistik from Semarang sent by the goods sender. This is in accordance with article 10 paragraph (2) letter i Government Regulation Number 15 Year 2013 concerning Regulation Number 38 Year 2009 concerning Postal Keywords: Standard Agreement, Factors, Responsibility, Delivery of Goods